Development of a new paradigm in biochemical engineering: Predicting the genetic regulation of aromatic pollutants degradation - Tsipa, Argyro; Koutinas, Michalis; Mantalaris, Athanasios A.; Pistikopoulos, Efstratios N. (My University, 2014)
In this work, we study Pseudomonas Putida which is a metabolically versatile soil bacterium. Its significance lies not only on the fact that it can metabolise numerous industrially important aromatic compounds (Pieper et al., 2004) but on its biotechnological potential by producing a series of fine and bulk chemicals, resulting in a growing interest of studying specific metabolic pathways at the genetic expression and regulation levels (Ballerstedt et al., 2007). This bacterium has several strains, but we focus on mt-2 because it degrades efficiently toluene.
Keywords: Chromosome; Genetic regulation; TOL plasmid; Toluene degradation